HUBUNGAN ANTARA EFEKTIVITAS KOMITE AUDIT DAN TIMELINESS PELAPORAN PADA PERUSAHAAN TERDAFTAR DI BEI TAHUN 2012 - Benny Yosua Ridwan; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the association between audit committee effectiveness and timeliness of submission of audited financial statements the Indonesian Stock Exchange (IDX). The population  of  this  study  were  all  public  companies  which  were  listed  on  Indonesian  Stock Exchange (IDX).  Sampling  was  conducted  by  eliminating  companies  which  were  new  listed, delisted, use foreign exchange and provide incomplete or unavailable data. Data were collected by downloading annual reports of all listed companies. Data from 358 companies can be used for analysis. The data analysis done by using regression model with ordinary least squares (OLS) methods to test factors influencing timeliness of reporting. IBM SPSS Statistics 22 had been used for analyzing. The result shows that audit committee effectiveness is likely to improve timeliness of financial reporting which is taken by companies to publicly release audited financial statements to the stock exchange. The result can be used as consideration by companies to improve audit committee effectiveness in order to enhance timeliness of financial reporting and to comply with Indonesian Stock Exchange regulation.